Fluvial dynamics and limnological characterization of cedro stream, president Prudente-SP - Degrande, Edmiler José Silva [UNESP]; Firmino, Glauber Verner [UNESP]; Torres, Marco Aurélio Neri [UNESP] (Revista Brasileira de Geografia Fisica, 2020)
A B S T R A C T The need for studies on environmental issues, such as water resources, is increasingly essential as a way of mitigating the adverse impacts caused by human actions. In this sense this article aims to analyze the river dynamics and its relationship with the limnological characteristics of the Cedro stream located in the city of Presidente Pru dente-SP. For this, this study evaluated three cross sections located in the high, medium and low course of this lotic environment. Samples were collected in the field of the main parameters associated with the channel hydraulic geometry, such as flow (Q), width (w), depth. (d), and velocity (v). For the limnological characterization of the stream in question we collected information about the Hydrogenionic Potential (pH), with the aid of a pH meter, and the Turbidity (for which a turbidimeter was used), as well as the collection of suspended sediment and bed. The evaluation of the suspended and bottom detrimental load occurred at the Laboratory of Geology, Geomorphology and Water Resources of the Universidade Estadual Paulista (UNESP), Presidente Prudente-SP campus. The results show that both the river dynamics and the limnological variables analyzed have been suffering from land use in the basin, resulting in the entry of allochthonous material of technogenic origin, promoting changes in the fluvial system adjustment and changes in the physical and chemical characteristics of the water. Thus, the study has been shown to be effective in correlating the data of hydraulic geometry and limnology in the environmental assessment of the area in question.
Dinâmica fluvial e caracterização limnológica do córrego do cedro, presidente Prudente-São Paulo/ Brasil
Keywords: Environmental diagnosis; Hydraulic geometry; Limnology